Developing mobile taxation accounting dictionary application: Augmenting speaking proficiency in project-based learning - Chandra Handayani, Luh Nyoman; Sukerti, Gusti Nyoman Ayu; Bayu Wicaksana, Ketut Arya; Adi Nugroho, I Made Riyan; Subiyanto, Paulus (Journal of English Language Teaching Innovations and Materials (Jeltim), 2024)
This study aims to investigate and develop a mobile tax accounting dictionary that functions as a self-learning tool for improving speaking competence through project-based learning. The dictionary was created based on the ADDIE Model (analysis, design, development, implementation, and evaluation). The application was developed utilizing the Waterfall approach, PHP programming language, and the SLIM framework. The application covered a wide range of tax accounting terms with bilingual sample sentences, learning materials focusing on grammatical constructions utilized in business meeting presentations, an evaluation section featuring vocabulary placement tests, and exercises at varying difficulty levels. During the implementation phase, a quasi-experimental approach was employed using a pretest-posttest control group design with 52 participants from the Accounting Taxation Study Program. To evaluate the impact of the dictionary application on student learning achievement, the speaking scores of the students were analyzed using the Kolmogorov-Smirnov test and the SPSS Statistics 25 program. The data analysis, specifically the independent Samples Test output table, revealed a significant difference (Sig value 0.05) between the results of the control and treatment classes. Consequently, the self-learning Taxation Accounting Dictionary application produced in this study was an excellent aid for boosting students"™ speaking skills, as evidenced by improved performance after using the application.